2017
DOI: 10.1016/j.rmed.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Serological study of Bordetella Pertussis, Mycoplasma Pneumonia and Chlamydia Pneumonia in Iranian hajj pilgrims with prolonged cough illnesses: A follow-up study

Abstract: Even though some rises and falls occurred in the antibodies titer, the variations could hardly be attributed to coughs in this study. Indeed, the variation of antibodies had no meaningful relationship with clinical factors. In this regard, further studies are needed to clarify the reason for the so-called "hajj coughs", but epidemiological studies will be difficult to do until easier and more reliable methods become available for accurate diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Overall, the prevalence of cough ranged from 1.9% in domestic and international pilgrims in 1999 [13] to 91.5% in Malaysian pilgrims in 2007 [14,15] ( Table 3). More recent studies, conducted in different populations of pilgrims during the 2011-2014 Hajj seasons, reported prevalence of cough ranging from 46.3% to 86.8% [16][17][18][19][20][21][22][23][24]. These studies also reported a comparable prevalence of sore throat ranging from 34.7% to 91% among pilgrims [16][17][18][19][20][21][22][23].…”
Section: Cohort Studies Addressing the Prevalence Of Respiratory Tracmentioning
confidence: 88%
See 1 more Smart Citation
“…Overall, the prevalence of cough ranged from 1.9% in domestic and international pilgrims in 1999 [13] to 91.5% in Malaysian pilgrims in 2007 [14,15] ( Table 3). More recent studies, conducted in different populations of pilgrims during the 2011-2014 Hajj seasons, reported prevalence of cough ranging from 46.3% to 86.8% [16][17][18][19][20][21][22][23][24]. These studies also reported a comparable prevalence of sore throat ranging from 34.7% to 91% among pilgrims [16][17][18][19][20][21][22][23].…”
Section: Cohort Studies Addressing the Prevalence Of Respiratory Tracmentioning
confidence: 88%
“…Of the 277 papers identified 183 records were excluded after screening the title and abstract. Of the 94 full text articles reviewed, 61 were deemed suitable for inclusion in this review S. Benkouiten et al Travel Medicine and Infectious Disease 28 (2019) [15][16][17][18][19][20][21][22][23][24][25][26] [27] (continued on next page) according to the inclusion/exclusion criteria. The results of the search strategy are shown in Fig.…”
Section: Included Studiesmentioning
confidence: 99%
“…The size of such gatherings increases the risk of certain public health issues and requires special attention to mitigate these risks (WHO 2005). Without proper planning and foresight, such events can put a strain on the health response resources of the community or country hosting the event, as well as a strain on global health responses, since these attendees are a part of a global population with diverse countries of return and origin (Leangapichart et al 2017;Khan et al 2017;Rahimian and Hosseini 2017;Cobbin et al 2017;WHO 2015). Events such as the Olympic Games, political rallies, and religious assemblies like Hajj are examples of mass gatherings that attract a large number of people (WHO 2015).…”
Section: Introductionmentioning
confidence: 99%